“Industry 4.0” Digital Strategy, and the Challenges for Adoption the Technologies Led by Cyber-Physical Systems - da Silva, Fernando Lima [UNESP]; Barriga, Gladys Dorotea Cacsire [UNESP] (Springer Nature, 2020)
The Brazilian’s manufacturing sector suffered a downturn due its recent economic crisis, reaching a negative growth rate of 8.48% in 2015. A proposed solution for improving performance in the manufacturing sector, and consequently developing several economies, such as Brazil, is the adoption of the digital strategy known as Industry 4.0. Since 2011, when this strategy was presented during Hannover Messe, in Germany, it is being considered as fourth industrial revolution, as a result of the developing new digital technologies and principles of implementation. However, to deployment of Industry 4.0, the manufacturing will face a number of challenges, such as related to technical, strategical and organizational contexts. The most frequent challenges are sorted by technical issues and demand for systems in CPS (Cyber-Physical Systems) technology. To benefit the manufacturing sector, the challenge of adoption CPS technologies, on real cases should be analyzed. The aim of this article is to present an international literature review about the challenges of Industry 4.0 on manufacturing sector. The literature does not present yet a broad study for identifying the challenges in this sector. As result, was discovered that there is a gap in the literature in the identification of systems solutions, simulated and or applied in the real context, which meet the requirements of CPSs, due to the low level of maturity of this technology. Developing algorithms of CPS and the related technologies of Industry 4.0, beside meet the new production demand is the fundamental challenge in the search for a digital and efficient industry.
Keywords: Challenges; Digital technology; Industry 4.0; Manufacturing strategy